2014
DOI: 10.1021/nl504079q
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive DNA-Peptide Nanotubes Enhance the Differentiation of Neural Stem Cells Into Neurons

Abstract: We report the construction of DNA nanotubes covalently functionalized with the cell adhesion peptide RGDS as a bioactive substrate for neural stem cell differentiation. Alteration of the Watson–Crick base pairing program that builds the nanostructures allowed us to probe independently the effect of nanotube architecture and peptide bioactivity on stem cell differentiation. We found that both factors instruct synergistically the preferential differentiation of the cells into neurons rather than astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 65 publications
0
118
0
1
Order By: Relevance
“…Furthermore, conjugation of targeting devices (monoclonal antibodies, [15][16][17] aptamers, [18][19][20] or peptides) [21] enables selective deliveryo fD NA vehicles to specific sites. [9,13,22,23] To release the cargo from the carrier, installation of an active devicet hat responds to externals timuli such as light, pH, or redox is required. Several stimuli-responsive devices based on conventional delivery platforms such as liposomes and micelles have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, conjugation of targeting devices (monoclonal antibodies, [15][16][17] aptamers, [18][19][20] or peptides) [21] enables selective deliveryo fD NA vehicles to specific sites. [9,13,22,23] To release the cargo from the carrier, installation of an active devicet hat responds to externals timuli such as light, pH, or redox is required. Several stimuli-responsive devices based on conventional delivery platforms such as liposomes and micelles have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[57] Stupp and coworkers reported the design of a DNA nanotube, which enhanced the differentiation of neural stem cells into neurons (Figure 13C). [234] The DNA nanotubes are self-assembled from five strands, one of which was functionalized by the RGDS sequence. They demonstrated that the co-assembled bioactive DNA/peptide-DNA supramolecular nanostructure promoted the cell adhesion and differentiation.…”
Section: Applications Of Supramolecular Biofunctional Materialsmentioning
confidence: 99%
“…, RGDs), which offered a facile pathway to investigate the effects of nanotube architecture and peptide bioactivity in cellular function (Fig. 19a) [327]. DNA origami is another promising approach to create nanoarchitectures and decorate specific functionalities at precise and controlled locations, which not only can help to understand the function of individual moieties, but also can controllably emulate cellular microenvironment.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…(ii, iii) Characterization of generated multiscale PCL nano/micro fiber and in vitro cellular reaction of PCL random multiscale fibers coated with Ch-HA. Reproduced with permission from: (a) [327], (b) [330]. …”
Section: Figurementioning
confidence: 99%